2014
DOI: 10.1093/esr/jcu064
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association of Religious Context with Giving to Non-Profit Organizations

Abstract: Why do citizens in religious groups and more religious countries give money to charitable causes? In this article we aim to theoretically and empirically unravel the influence of religious composition on giving to non-profit organizations across countries. Building on theories and research in sociology, social psychology, and economics we formulate hypotheses about individual-and contextuallevel differences in engagement in religious and secular charitable giving. We test our hypotheses with multi-level analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…If this effect predominates, then members of minority religious groups would be more likely to help strangers. Wiepking, Bekkers, and Osili () find support for this theory for both secular and religious charitable giving, and Bennett () finds this effect in terms of formal volunteering. Although the theoretical literature could support either a negative or positive effect of membership in a religious minority group, the two studies prior to ours found that members of minority religious groups were more likely to be prosocial, so we test this hypothesis: H3:People who belong to a religious minority group in a society will have a higher likelihood of helping a stranger. …”
Section: Review Of the Literaturementioning
confidence: 96%
See 2 more Smart Citations
“…If this effect predominates, then members of minority religious groups would be more likely to help strangers. Wiepking, Bekkers, and Osili () find support for this theory for both secular and religious charitable giving, and Bennett () finds this effect in terms of formal volunteering. Although the theoretical literature could support either a negative or positive effect of membership in a religious minority group, the two studies prior to ours found that members of minority religious groups were more likely to be prosocial, so we test this hypothesis: H3:People who belong to a religious minority group in a society will have a higher likelihood of helping a stranger. …”
Section: Review Of the Literaturementioning
confidence: 96%
“…However, higher levels of religious activity in a society may lead to a greater diffusion of prosocial norms that would increase the prosocial behavior of all people within a society, irrespective of whether they are religious or not. Cross‐national studies by Ruiter and De Graaf () and Lam () find that religious norms affect volunteering even among the nondevout, and Wiepking, Bekkers, and Osili () find a similar effect on religious and secular giving. Borgonovi () finds an effect of religious norms on the nondevout in a U.S. study.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to recognize that overall rates of volunteering and donating may be inflated in self-report surveys (Abraham, Helms, & Presser, 2009;Bekkers & Wiepking, 2011a). It may also be the case that incidental and irregular giving is underreported in the ESS (Wiepking, Bekkers, & Osili, 2014). 8.…”
Section: Notesmentioning
confidence: 99%
“…Broadly speaking, donors are more likely to be female, older, married, religious, educated, and wealthy (Bègue, 2014;Bekkers & Wiepking, 2011c;Brooks, 2003b;Choi & DiNitto, 2012;Forbes & Zampelli, 2013;Helms & Thornton, 2012;Herzog & Yang, 2018;Hughes & Luksetich, 2008;Korndörfer, Egloff, & Schmukle, 2015;Leslie, Snyder, & Glomb, 2013;Manesi, Van Lange, Van Doesum, & Pollet, 2018;McGregor-Lowndes & Crittall, 2014;Mesch, Brown, Moore, & Hayat, 2011;Mesch, Osili, Ackerman, & Dale, 2015a;Mesch, Rooney, Steinberg, & Denton, 2006;Midlarsky & Hannah, 1989;Neumayr & Handy, 2017;Rajan, Pink, & Dow, 2009;Rooney, Mesch, Chin, & Steinberg, 2005;Sibley & Bulbulia, 2015;Stavrova & Siegers, 2014;L. Steinberg & Monahan, 2007;Tremblay-Boire & Prakash, 2017;Vaidyanathan, Hill, & Smith, 2011;Wiepking & Bekkers, 2012;Wiepking, Bekkers, & Osili, 2014;Wiepking & James, 2013;Wiepking & Maas, 2009).…”
Section: Who Gives To Charity?mentioning
confidence: 99%